2007
DOI: 10.4103/0972-5229.33388
|View full text |Cite
|
Sign up to set email alerts
|

Study of risk factors and prevalence of invasive candidiasis in a tertiary care hospital

Abstract: Introduction: The frequency of invasive mycoses has increased dramatically during the past two decades owing to medical advances such as intensive cancer chemotherapy, broad-spectrum antimicrobial therapy, invasive medical devices, organ transplantation, human immunodeÞ ciency virus (HIV) disease epidemic and an expanding aging population. There were few Indian studies regarding the incidence and risk factors for candidemia. Hence the aim of this work was to evaluate the changes in the prevalence of candidemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
10
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 33 publications
8
10
1
Order By: Relevance
“…Confirming earlier reports (Bassetti et al 2007;Blumberg et al 2001;Bross et al 1989;Sung et al 2001;Wey et al 1989), our study showed that renal insufficiency was independently related to candidaemia in the logistic regression model. Our study did not find other significant host-related factors, which is in contrast to other studies that reported diabetes mellitus (Michalopoulos et al 2003;Wu et al 2014), HIV infection (Chowta et al 2007;Petrosillo et al 2002), malignancy (Zaoutis et al 2010) and prematurity (Saiman et al 2000;Wu et al 2013), as significant risk factors. This could possibly due to several factors -our small sample size, particularly for HIV infection and prematurity; different study population by Zaoutis et al (2010) who included only paediatric patients and diabetes mellitus being too prevalent in our population that it is present too often in both groups.…”
Section: Discussioncontrasting
confidence: 56%
“…Confirming earlier reports (Bassetti et al 2007;Blumberg et al 2001;Bross et al 1989;Sung et al 2001;Wey et al 1989), our study showed that renal insufficiency was independently related to candidaemia in the logistic regression model. Our study did not find other significant host-related factors, which is in contrast to other studies that reported diabetes mellitus (Michalopoulos et al 2003;Wu et al 2014), HIV infection (Chowta et al 2007;Petrosillo et al 2002), malignancy (Zaoutis et al 2010) and prematurity (Saiman et al 2000;Wu et al 2013), as significant risk factors. This could possibly due to several factors -our small sample size, particularly for HIV infection and prematurity; different study population by Zaoutis et al (2010) who included only paediatric patients and diabetes mellitus being too prevalent in our population that it is present too often in both groups.…”
Section: Discussioncontrasting
confidence: 56%
“…was the third most common cause of blood stream infections in HIV patients 24 . From India Chowta et al 25 also reported HIV as one of the major predisposing risk for candidemia. The duration of hospital stay, antibiotic prophylaxis and treatment, level of immunosuppression, presence of other opportunistic infection and other clinical types of candidiasis increases the risk of candidemia in HIV infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…[3] In India, C. tropicalis is now the most common cause of nosocomial candidemia. Epidemiological studies have implicated C. tropicalis in as many as 67-90% of cases of [14] New Delhi Prolonged hospital stay, use of broad-spectrum antibiotics, CVCs, mechanical ventilation and TPN Chowta et al 2007 [57] Mangalore Intravenous catheters (most common), prolonged use of antimicrobials and HIV infection Indian Journal of Medical Microbiology vol. 30,No.…”
Section: Species Distribution Among Candida Isolates From Bloodmentioning
confidence: 99%